PROGRAM REBAS (REMAJA BEBAS ASAP ROKOK) MENCEGAH DAN MENGATASI ADIKSI ROKOK PADA REMAJA MASJID NURUL HUDA DESA PUNGGUR KECIL KECAMATAN SUNGAI KAKAP KABUPATEN KUBU RAYA - Sri Ariyanti; Uji Kawuryan; Hartono (TRIMAS: Jurnal Inovasi dan Pengabdian Kepada Masyarakat, 2021)
The Global Youth Tubacco Survey (GYTS) states that Indonesia as the country with the highest teenage smoking rate of 2014, is mostly male with age 12-13 years when first smoked and female at 14-15 years old. Based on data indicated by the Ministry of Health that the prevalence of adolescents aged 16-19 years increased 3-fold from 1995 from 7.1% to 20.5% in 2014. According to the result, this study aimed to prevent and address smoking addiction in adolescents by using a program that focuses on preventive and curative that is by using innovation program of REBAS (Remaja Bebas Asap Rokok). The participants who involved in the program were 38 students. The REBAS program given to the participants used the method of group discusion forums, where participants were given pretest and post test to know the level of knowledge about smoking, and were invited to discuss through played a video and discused in a small groups accompanied by two facilitators. The event ended with a material review and pronunciation of the REBAS pledge that was spoken together. Conclusion: After the ongoing program of REBAS, participants can realize the importance of the dangers of smoking and the importance of improving anti-smoking movement early on. Recommendation:There is needs of regular program for prevention smoking to adolescents.